Maturation Age: Another Dropout Factor? - Thomas, William D. (Canadian Journal of Counselling and Psychotherapy, 2012)
Dropouts from school are a serious problem and many interrelated factors have been identified. Students who drop out often see the school as hostile and rejecting. In a longitudinal study carried out in an Edmonton high school data were gathered from 196 grade-ten students. Of these, 130 graduated, 55 dropped out, and 11 transferred out. One item of information for the 185 students studied was an estimate of maturation age as shown by growth spurts from height and weight charts. The maturation age for dropouts was significantly earlier than the maturation age of those who graduated. This difference leads to speculation as to why this is so. Do those who mature early see the school as more hostile and rejecting?